3D design basics : book three - Fullmer, Donna Lynne, ....- (New York : Fairchild, 2013)
3D Design Basics explores basic three-dimensional options for presenting design ideas, including models, paraline drawings, and perspective drawings. Students will be exposed to a variety of model-building tools and methods and learn how to start designing with quick rip-and-tear models.
Keywords: Industrial design -- Data processing; Architectural design -- Data processing; Three-dimensional display systems